Impact of Blood Pressure on Retinal Microvasculature Architecture Across the Lifespan: The Young Finns Study. (February 2015) - Tapp, Robyn J.; Hussain, S. Monira; Battista, Josephine; Hutri‐Kähönen, Nina; Lehtimäki, Terho; Hughes, Alun D.; McG Thom, Simon A.; Metha, Andrew; Raitakari, Olli T.; Kähönen, Mika
Abstract Objective The present study examined the impact of BP from childhood to mid‐adulthood on retinal microvascular architecture. Methods The Cardiovascular Risk in Young Finns Study included children aged 3–18 years, from five Finnish University cities, with participants chosen randomly from the national population registrar from those areas. The age of participants included in the current analyses in childhood (1980) ranged from three to nine years and in mid‐adulthood (2011) ranged from 34 to 40 years (complete data n = 657). Measures of retinal microvasculature architecture measured in adulthood included diameters, tortuosity, lengths, and LDR. Results Regression analysis showed a strong negative association between childhood systolic BP and adult arteriolar diameter (standardized regression coefficient [β] −0.300; p < 0.001) and with change in systolic BP from childhood to adulthood (β = −0.249; p < 0.001). For arteriolar tortuosity, there was a strong positive association between childhood systolic BP and adult arteriolar tortuosity (β = 0.154; p < 0.001) and no association with change in systolic BP from childhood to adulthood (β = 0.072; p = 0.110). Conclusions High BP in childhood and increased BP from childhood to adulthood impacts on retinal microvascular architecture in mid‐adulthood.